Gut microbiota and thyroid diseases - summary of current knowledge - Aleksander Daniluk; Kaja Iwaniuk; Martyna Wojda; Magdalena Świstowska; Aleksandra Wielgosz (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: The gut microbiota is a diverse collection of microorganisms that coexist in the human intestine. Disorders in its structure leads to dysregulation of huge number of organs, including the thyroid. This review summarizes the latest findings regarding the links between gut microbiota and common thyroid diseases: Hashimoto's thyroiditis, Graves' disease and thyroid cancer. Materials and methods: This review was based on the PubMed and Google Scholar databases, using keywords: "gut microbiota AND thyroid/Hashimoto/Graves/thyroid cancer", "Graves' disease", ,,Hashimoto thyroiditis". Description of knowledge: Gut dysbiosis can contribute to autoimmune thyroid diseases by influencing micronutrient availability and immune regulation. Specific bacterial species may impact Hashimoto's development by regulating neurotransmitters and hormone secretion. In Graves' disease, significant changes in gut microbiota suggest their potential role in autoimmune processes. Research on gut microbiota in thyroid cancer suggests potential diagnostic tools and implicates gut microbiota alterations in tumor development. Conclusions: Significant gut microbiota changes are observed in Hashimoto's thyroiditis, Graves' disease, and thyroid cancer compared to healthy individuals, indicating a possible association. However, the exact mechanisms remain unclear, necessitating further research to understand how microbiota alterations contribute to these diseases.